A multi-dimensional approach to consumer motivation: exploring economic, hedonic, and normative consumption goals. Issue 1 (11th January 2016) - Barbopoulos, Isak; Johansson, Lars-Olof
Abstract : Purpose: – The purpose of the present research is to explore the (multi-) dimensionality of the highly influential gain, hedonic and normative master goals. Despite being important drivers of consumer behavior, few attempts have been made to incorporate these goals into a single measure. Design/methodology/approach: – Across three studies, the dimensionality of the gain, hedonic, and normative master goals are explored (Study 1), confirmed (Study 2) and validated (Study 3). Findings: – A structure of five distinct sub-goals emerged, which were shown to be related to the original higher-order goals: thrift and safety (related to the gain goal), moral and social norms (related to the normative goal) and instant gratification (related to the hedonic goal). These five dimensions were shown to have satisfactory convergent, discriminant and construct validity. Research limitations/implications: – The present research shows that consumer motivation is multi-dimensional, and that a distinction should be made not only between higher-order utilitarian, hedonic and normative determinants but also between their corresponding sub-goals, such as social and moral norms. A multi-dimensional approach to consumer motivation should prove useful in standard marketing research, as well as in the segmentation of consumer groups, products and settings. Originality/value: – The emergent dimensions encompass a broad range of research, from economics and marketing, to social and environmental psychology, providing consumer researchers and practitioners alike a more nuanced and psychologically accurate view on consumer motivation.